Menjelajahi Kegembiraan Multibahasa: Analisis Linguistik Pengalihan Kode dan Pencampuran Kode di Video YouTube Livy Renata: Tanya Jawab dengan Catheez - Abidah, Nabila Farah; Sabilillah, Margaretha Jihad Fitri; Habibah, Alfy Rifngatul (JURNAL LITERASI, 2023)
This paper aims to analyze code mixing and switching used in one of the question-and-answer YouTube videos between Livy Renata and Chateez, along with the types of code. In this study, researchers used theories by Muskeyn (2000) to analyze code-mixing types and theories by Holmes (2013) to analyze code-switching types. Musyken (2000) explained three types of code mixing: insertion, alternation, and congruent lexicalization. As for code-switching theory, Holmes explained three types of code-switching: tag switching, inter-sentential switching, and intra-sentential switching. This research raises the problem of what types of code-switching and code-mixing are used by Livy Renata and Catheez on the Livy Renata YouTube channel. There are several methods carried out by researchers in collecting data, such as video search, watching videos, listening to audio, and identifying code switching and code mixing. The researchers obtained that six sentences use code-mixing with insertion type, five sentence uses alternation type, and four sentence uses congruent lexicalization type. This research also shows the use of code-switching found in the video: there is a type of tag switching of 1 sentence, then a kind of inter-sentential switching of 4 sentence, and a type of intra-sentential switching of 1 sentences.